Assessment of Compost Maturity using The Static Respirometry Index - Gabriel Andari Kristanto; Syifa Aulia Rahmah (Reaktor, 2018)
To be used as organic fertilizer, compost must be stable and mature enough to ensure that it is safe for agricultural application. The stability and maturity of compost can be viewed from physical, chemical, and biological parameters. One of the biological parameters is the static respiration index (SRI). In many places, the SRI is applied as a representative indicator of the stability and maturity of compost but not in Indonesia compost standard of the SNI 19-7030-2004. This study aims to assess the index of the static respiration of composts and analyze their stability and maturity. The assessment was carried out on 10 compost samples sold in Jakarta and Depok. It is observed that 8 of 10 tested composts was stable and mature, with a static respiration index of 0.61–1.35 mg O2 g-1 VS h-1. One of the 10 composts was very stable and very mature, with a static respiration index of 0.46 mg O2 g-1 VS h-1 and 1 compost was unstable and immature, with an index of 1.79 mg O2 g-1 VS h-1. The results indicated that re-composted for seven days was adequate to make the compost more stable and mature than the initial state. Since maturity is not described by a single property, it is great assurance for the compost producer and end user in Indonesia that not only physical and chemical characteristics are used as indicator for compost stability and maturity but also biological indicator such as SRI. Keywords: compost; maturity; stability; static respiration index